A case of multiple serous cystadenoma of pancreas. (December 2020) - Sekiguchi, Naoko; Nakashima, Shinsuke; Koh, Masahiro; Ueda, Masami; Tsuda, Yujiro; Tanida, Tsukasa; Matsuyama, Jin; Ikenaga, Masakazu; Yamada, Terumasa
Abstract: Introduction: Typically, SCN is single and doesn't invade around tissue. In our case, tumors were multiple and had gradually grown and caused vein stenosis. This is extremely rare and unique resected multiple SCN case. In addition, I report that it was thought to be educational that even benign tumors could cause such changes. Presentation of case: A 60-year-old female was diagnosed with 3 multilocular cystic tumors in distal pancreas by contrast enhanced computed tomography (CT) at the preoperative staging for rectal neoplasm. The diameters of cystic tumors were 22/23/29 mm. The CT showed that the tumors had multiple internal septa enhanced in the arterial phase and the second tumor contained internal calcifications located centrally. The main pancreatic duct was not dilated. Although SCN often occurred single and multiple SCN was very rare, we diagnosed that the tumors were suspected microcystic type SCN because they had typical image findings. So, we planned to follow up every six months after resection for rectal neoplasm. 2 years and half later, they had gradually grown, and splenic vein stenosis appeared. The pancreatic parenchyma atrophy and dilatation of the main pancreatic duct had been gradually progressing. We performed distal pancreatectomy because of possibility of malignancy. The histopathological findings showed that 2 cystic tumors the side of pancreatic head had a connection and had typical findings of SCA of pancreas. The other tumor was independent from two tumors. They had no malignant findings. Discussion: At first, we expected tumor invasion had caused the changes. But tumors had no malignant findings, so we considered that compression from the tumor had caused stenosis, and obstructive pancreatitis had induced the pancreatic parenchyma atrophy. Conclusion: We learned from this case that not only invasion but also compression caused vein stenosis and pancreatic duct dilation. Highlights: Multiple serous cystic neoplasms are rare tumors. The tumors had gradually grown and main pancreatic duct dilatation had appeared. We performed laparotomy because we couldn't deny local infiltration. The main pancreatic duct dilatation had been caused by the compression. This is unique that even benign tumors could cause pancreatic duct dilatation.